Towards Happy Relief Campers: Surfacing Psycho-social Issues, Conflicts and Other Problems for Flood-affected Residents and Officials in Kuruwita, Sri Lanka - Amarakoon, Vihanga; Trafford, Julie; Udeshika, Thilakshi; Amarasekara, Dulshara Sachini; Wickramasinghe, Deepthi (Elsevier BV, 2024)
Floods are a common natural disaster globally, particularly in Asia, with significant impacts on humans and property. However, the psycho-social issues and conflicts faced by flood-affected residents and government officials who support them are less researched in the existing literature, particularly within the Sri Lankan context. This study aimed to explore the nature and reasons for conflicts and psycho-social issues arising for flood-affected residents within the Kuruwita Divisional Secretariat (DS) of the Kalu river basin of Sri Lanka following the 2017 flood event. It also investigated the problems faced by the government officials during flood events. The research employed a key informant mixed-method approach, with government officials participating in a two-part workshop where they answered a questionnaire and engaged in a poster presentation. According to the results, the main reason for conflicts was limited or uneven distribution of compensation, and officials faced problems when performing their duties during flood events, often related to the distribution of compensation and tensions arising from racial/cultural differences. The study concluded that it is crucial for the Sri Lankan government to provide solutions to the issues and problems faced by flood-affected residents and government officials who support these communities. Further research and policy development are needed for effective flood risk reduction within the Kalu river basin.
Keywords: 4404 Development Studies; 4406 Human Geography; 44 Human Society; 0502 Environmental Science and Management; 1117 Public Health and Health Services; 1604 Human Geography